Low-cost, self-made CAD/CAM-guiding system for mandibular reconstruction. (June 2018) - Dell'Aversana Orabona, Giovanni; Abbate, Vincenzo; Maglitto, Fabio; Bonavolontà, Paola; Salzano, Giovanni; Romano, Antonio; Reccia, Alfonso; Committeri, Umberto; Iaconetta, Giorgio; Califano, Luigi
Abstract: Facial symmetry, as well as function, remains the big challenge for surgeons who attempt mandibular reconstruction. Nowadays several studies recommend the use of computer aided surgery (CAS) and CAD/CAM technology to guide mandibular segmental osteotomies and reconstruction using free fibula flap. Although these systems have radically changed the way of doing mandibular reconstructive surgery, they are expensive and require extended periods of time for prototypation. This may be an important limitation in case of malignant neoplasms which require short-term treatment. The aim of our study is to investigate the reliability and efficiency of a protocol to obtain cutting guides produced in a "homemade" way. This study includes four consecutive patients who underwent a segmental mandibulectomy and fibula osteo-cutaneous free flap reconstruction for oral squamous cell carcinoma between January and September 2016. The CAD/CAM system algorithm proposed was based on the use of free open source software for digital planning and 3D layer plastic deposition printer. A cost of about 3 Euro for each case was estimated. An average mean distance between 3D preoperative and postoperative mesh points of 1.631 mm and a standard deviation of 5.496 mm has been demonstrated by 3D volume overlay analysis. Overlapping results with much shorter prototyping time was required with the in-house procedure described as compared to the available commercial system. In conclusion, we expect that this technique will reduce operative time and cost however further study and large series are needed to confirm our results and better define the applicability in everyday surgical practice. Highlights: Current mandibular reconstruction systems require extended periods of time for prototypation. The algorithm proposed was based on open source software for planning and 3D printer. Our algorithms provide overlapping results with current commercial systems in term of accuracy. Time required to manufacture our cutting guides could potentially be reduced by 24 h. With this in-house procedure operative time and cost will be reduced.